The Political Economy of Hunger: Volume 2: Famine Prevention 1991
DOI: 10.1093/acprof:oso/9780198286363.003.0006
|View full text |Cite
|
Sign up to set email alerts
|

Market Responses to Anti-hunger Policies: Effects on Wages, Prices and Employment

Abstract: * I have had useful discussions on some of these issues with Jim Boyce S. Bramhe, V.M. Dandekar, N.S. Jodha, Kiran Moghe, Amartya Sen, R.M. Sundrum, Dominique van de Walle, and Tom Walker. I am particularly grateful to Jean Dreze for his detailed comments on the paper.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 43 publications
1
32
0
Order By: Relevance
“…The study concludes that a sharp reduction in the share of poor participation was compensated by higher agricultural wage. A similar conclusion to support for the substantial multiplier effect is drawn by Ravallion (1990) who assumes the urban/rural dualistic economy with mobility between a rural sector where wage is flexible and an urban sector where wage is fixed. However, drawing upon 1987-89 data, Ravallion et.…”
Section: Indirect Effects Of the Egssupporting
confidence: 65%
“…The study concludes that a sharp reduction in the share of poor participation was compensated by higher agricultural wage. A similar conclusion to support for the substantial multiplier effect is drawn by Ravallion (1990) who assumes the urban/rural dualistic economy with mobility between a rural sector where wage is flexible and an urban sector where wage is fixed. However, drawing upon 1987-89 data, Ravallion et.…”
Section: Indirect Effects Of the Egssupporting
confidence: 65%
“…36 Following Ravallion's [1991a] classification, one difficulty is that only a component of direct transfer benefits (that is, net EGS earnings) is considered. While these benefits are not unimportant, other benefits matter too.…”
Section: Targeting Of Egsmentioning
confidence: 99%
“…Economists have studied the effects of such program on wages and private sector hiring. Ravallion (1987) and Basu et al (2009) show that government hiring may crowd out private sector work and lead to a rise in equilibrium private sector wages. Recently various papers have shown that there has been an increase in rural wages in India due to workfare (Imbert and Papp, 2015;Berg et al, 2012;Azam, 2012).…”
Section: Introductionmentioning
confidence: 99%